Photophysiological response of glacier ice algae to abiotic stressors - Jensen, Marie Bolander; Turpin-Jelfs, Thomas; Tranter, Martyn; Benning, Liane G.; Anesio, Alexandre M. (Frontiers in Geochemistry, 2024)
The glacier ice algae Ancylonema alaskanum and Ancylonema nordenski öldii grow in harsh dynamic environments on bare ice surfaces. In these environments, they contribute to the continuous darkening of the ice surface, which in turn accelerates the ice melt. However, investigation into their adaptation and resilience in these environments is necessary in order to understand their robustness and potential for increasing the intensity of blooms. In this study it was examined how variations in environmental parameters such as pH, salinity, light and temperature impacted the photophysiology of the glacier ice algae during a bloom in Greenland.Through in situ incubations and pulse-amplitude-modulation (PAM) fluorometric measurements, the photophysiological responses of algal cells were assessed. Results suggest that light intensity significantly influences glacier ice algae photophysiology, with cells exhibiting better performance (in terms of a higher α and F v /F m ratio) under lower light intensity. Moreover, while light emerges as the primary driver of photophysiology, glacier ice algae demonstrate tolerance to a broad range of pH and temperatures four times higher than those experienced during Greenland's summer.